Причинно-наслідковий штучний інтелект і інтернет речей - Кирсанов, О. О.; Кривенко, С. А. (ХНУРЕ, 2025)
The document discusses an experiment involving dynamic administration of medications using causal artificial intelligence, specifically Amazon SageMaker, to optimize treatment protocols. The study aims to experiment with dynamic administration of medical drugs to patients using causal artificial intelligence to optimize treatment protocols and improve overall treatment outcomes. The experiment utilized Amazon SageMaker methods, which provide tools to automate processes, optimize workflows, and create machine learning models. The results indicated that the proposed AI model could optimize medication dosages, leading to a significant improvement in the overall treatment effect by more than 20%
Keywords: інтернет речей; Amazon SageMaker